2015
DOI: 10.1308/003588415x14181254789169
|View full text |Cite
|
Sign up to set email alerts
|

Major cardiothoracic trauma: Eleven-year review of outcomes in the North West of England

Abstract: INTRODUCTION Up to 15% of patients with cardiothoracic trauma require emergency surgery, and death can be prevented in a substantial proportion of this group. UK reports have emphasised the need for improvement in this field. We assessed major cardiothoracic trauma (MCT) outcomes in North West England over 11 years. METHODS The database from the Trauma Audit and Research Network was used to retrieve data for all patients who had suffered MCT between 2000 and 2011 in North West England and the findings analysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
(20 reference statements)
1
8
0
3
Order By: Relevance
“…Penetrating heart injuries represent a significant mortality cause, and can be challenging either from the therapeutic or the diagnostic point of view, since they can be asymptomatic or oligosymptomatic for a variable period after a trauma occurs 6,11,14 . Most studies show that young men are the most struck by penetrating heart injuries, which is in consonance with our outcomes 5,7,8,[14][15][16][17][18] .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Penetrating heart injuries represent a significant mortality cause, and can be challenging either from the therapeutic or the diagnostic point of view, since they can be asymptomatic or oligosymptomatic for a variable period after a trauma occurs 6,11,14 . Most studies show that young men are the most struck by penetrating heart injuries, which is in consonance with our outcomes 5,7,8,[14][15][16][17][18] .…”
Section: Discussionsupporting
confidence: 88%
“…The most frequent mechanism among patients operated due to penetrating heart traumatism is stab wounds, in a proportion ranging from 39% to 81.4% 3,7,8,15 . Necropsy research suggests that firearm wounds (GSW) are the most frequent 2 ones.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the study conducted by Awais et al (12) penetrating and blunt thoracic trauma was reported in 104 (50.2%) and 103 (49.8%) cases respectively with nearly equal distribution. Furthermore, Khorsandi et al (13) study showed more prevalence in penetrating trauma patients than those with blunt trauma among studied patients.…”
Section: Discussionmentioning
confidence: 83%
“…Men are more inclined to trauma and injuries as they pursue riskier activities at the workplace and at home (e.g. [31, 32]), whereas burns are a leading cause of injuries in children in Mongolia [33, 34]. In the BTC we did observe a colonization rate exceeding 50% in all age groups though significantly less in children.…”
Section: Discussionmentioning
confidence: 76%